Análisis Del Comportamiento De Las Precipitaciones En Quevedo - Ecuador, Para La Planificación De Cultivos - Oscar Caicedo-Camposano; Dalton Cadena-Piedrahita; Luis Alcívar-Torres; Adela Veloz-Paredes; Franklin Montecé-Mosquera (European Scientific Journal, ESJ, 2016)
The work was performed with the aim of knowing the rainfall of the city of Quevedo in Ecuador, to improve the calendars of short-cycle crops, since this information is commonly required by farmers in the area and agricultural professionals who work as technical advisers. Processing a series of recordings of rainfall of 35 years belonging to the Pichilingue Weather Station of the National Institute of Meteorology and Hydrology located on the premises of the National Agricultural Research Institute, the methodology applied was focuses on the determination of statisticians as the average, Standard Deviation, Variance, coefficient of variation, skewness and kurtosis coefficient; then based on the average are determined wet and dry periods the frequency and the intensity with which they occur. That also was detected in this town from 1980 to 2014 there were 10 dry periods and nine wet periods, which are presented with a frequency of 3,8 and 3,6 years respectively. Based on the results, the wet season is defined between the months of December to May and the dry season from June to November. The foil available average rain accumulated determined for the wet and dry periods has the following values: 953,3 mm, 2924,2 mm and an average of 2216,3 mm. Short-cycle crops of the area should be planted since the month of December to be exploited all the rain of the wet season.